OPINI PEMUSTAKA TENTANG LAYANAN PERPUSTAKAAN UNIVERSITAS RIAU DALAM MENUNJANG PROSES PERKULIAHAN MAHASISWA (Studi Pada Mahasiswa Fakultas Keguruan dan Ilmu Pendidikan) - Elvina "; Welly Wirman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Abstract Riau University Library is the library is good, this is proven by the best value reached in the accreditation of library by 2013 category "A". The existence of Riau University Library has the goal to support the process and associated library visitors. In line with awards by the University Library of the Riau, researchers interested in conducting research on library services University of Riau in the support process and associated students. This research was conducted with the objective to see how opinions about the services of library visitors Riau University Library in supporting the process and associated students of Faculty of teacher training and education. This study uses qualitative methods. That becomes the subject in this study constitute the entire informants who met the criteria needed in this study, among others, students of the Faculty of teacher training and educational sciences (FKIP) Riau University who visited the University Library University Library head of Riau, Riau, head of the Ministry, the head of the development of the collection, and Processing Staff and service references. Later became the object of research, namely Riau University library service in the support process and associated students FKIP University of Riau and data capture technique in this study using a deep observation and interviews and documentation. The result of the research shows that library visitors gave a positive opinion in terms of the availability of the means and infrastructure repair that is in the library of the University of Riau. It can be seen from the attitude displayed by library visitors such as feeling happy and comfortable when receiving the library services provided, the intensity of the visits students FKIP visited the University Library of Riau, and also understanding library visitors is good in understanding the procedures and rules that apply in the University Library. But in his Ministry, there are a few things that need to be improved in order to be assessed library visitors can enjoy maximum and get more information according to your needs, such as a welcoming and friendly service from librarian, more complete and developed a collection of existing library materials, provides some lack facilities such as plugs, and the need for a more intense socialization regarding the service provided University Library. Keyword: Opinion, Library Visitors, Library, Riau University Library, Librarian, and Students